Preserving the money of minors According to the provisions of Iraqi law and Islamic jurisprudence A comparative analytical study - Zuha Mohammed Saeed; Omer Riyadh Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
If it was originally that any human can excersise his financial and management rights, but but this rule unanswered exception when the man was a minor. As a minor can not exercise financial rights only through someone else is taking care of his economic rights, and that person is either a crown or a trustee or valuable, as the case stipulated by law, and the preservation of the minor money is the most important work that lies with the charge of his care, and conservation work either conservation work be physical or casity legal work, Perhaps the most prominent forms of litigation, arbitration, and the provisions of takes care of the minor non-power of attorney to represent him in the care of the minor money.